Translatome analyses by bio-orthogonal non-canonical amino acid labeling reveal that MR1-activated MAIT cells induce an M1 phenotype and antiviral programming in antigen-presenting monocytes - Jakob, Josefine; Kröger, Andrea; Klawonn, Frank; Bruder, Dunja; Jänsch, Lothar (Frontiers in Immunology, 2023)
MAIT cells are multifunctional innate-like effector cells recognizing bacterial-derived vitamin B metabolites presented by the non-polymorphic MHC class I related protein 1 (MR1). However, our understanding of MR1-mediated responses of MAIT cells upon their interaction with other immune cells is still incomplete. Here, we performed the first translatome study of primary human MAIT cells interacting with THP-1 monocytes in a bicellular system. We analyzed the interaction between MAIT and THP-1 cells in the presence of the activating 5-OP-RU or the inhibitory Ac-6-FP MR1-ligand. Using bio-orthogonal non-canonical amino acid tagging (BONCAT) we were able to enrich selectively those proteins that were newly translated during MR1-dependent cellular interaction. Subsequently, newly translated proteins were measured cell-type-specifically by ultrasensitive proteomics to decipher the coinciding immune responses in both cell types. This strategy identified over 2,000 MAIT and 3,000 THP-1 active protein translations following MR1 ligand stimulations. Translation in both cell types was found to be increased by 5-OP-RU, which correlated with their conjugation frequency and CD3 polarization at MAIT cell immunological synapses in the presence of 5-OP-RU. In contrast, Ac-6-FP only regulated a few protein translations, including GSK3B, indicating an anergic phenotype. In addition to known effector responses, 5-OP-RU-induced protein translations uncovered type I and type II Interferon-driven protein expression profiles in both MAIT and THP-1 cells. Interestingly, the translatome of THP-1 cells suggested that activated MAIT cells can impact M1/M2 polarization in these cells. Indeed, gene and surface expression of CXCL10, IL-1, CD80, and CD206 confirmed an M1-like phenotype of macrophages being induced in the presence of 5-OP-RU-activated MAIT cells. Furthermore, we validated that the Interferon-driven translatome was accompanied by the induction of an antiviral phenotype in THP-1 cells, which were found able to suppress viral replication following conjugation with MR1-activated MAIT cells. In conclusion, BONCAT translatomics extended our knowledge of MAIT cell immune responses at the protein level and discovered that MR1-activated MAIT cells are sufficient to induce M1 polarization and an anti-viral program of macrophages.